Bilateral split hand/foot malformation and inv(7)(p22q21.3). Issue 5 (May 1995) - Cobben, J M; Verheij, J B; Eisma, W H; Robinson, P H; Zwierstra, R P; Leegte, B; Castedo, S
Abstract : A boy with typical tetramelic split hands and feet is described. In addition, there was a large arteriovenous malformation of the right arm. Chromosome studies showed a pericentric inversion of chromosome 7: 46, XY, inv(7)(p22q21.3). Inspection of the extremities and chromosome studies in the parents were normal. This case confirms the suggested localisation of a locus, important for early limb differentiation, on the long arm of chromosome 7, most probably in the chromosomal region 7q21.2-7q21.3. Previously reported cases are reviewed briefly.